An analysis of Brazilian flight delays based on frequent patterns. (November 2016) - Sternberg, Alice; Carvalho, Diego; Murta, Leonardo; Soares, Jorge; Ogasawara, Eduardo
Highlights: We applied association rules and data indexing techniques to study flight delays. We originally studied Brazilian flight data for flight delays. Our research was guided by research questions to understand Brazilian flight system. We found the Brazilian flight network has difficulties to recover from previous delays. Abstract: In this paper we applied data indexing techniques combined with association rules to unveil hidden patterns of flight delays. Considering Brazilian flight data and guided by six research questions related to causes, moments, differences, and relationships between airports and airlines, we evaluated and quantified all attributes that may lead to delays, showing not only the main patterns, but also their chances of occurrence in the entire network, in each airport and airline. We observed that Brazilian flight system has difficulties to recover from previous delays and when operating under adverse meteorological conditions, delays occurrences may increase up to 216%.